Slope stability, retaining walls, and foundations : selected papers from the 2009 GeoHunan International Conference, August 3-6, 2009, Changsha, Hunan, China - Ge, Louis (Geotechnical special publication ;, 2009)
"This Geotechnical Special Publication contains 35 peer reviewed technical papers presented at the GeoHunan International Conference: Challenges and Recent Advancesin PavementTechnologies and Transportation Geotechnics, which took place in Changsha, Hunan, China, from August 3 to 6, 2009. This proceedings examines topics such as: soil stabilization; dynamic behavior of soils and foundations; earth retaining walls; and slope stability." "This publication will be valuable to geotechnical engineering professors and students, as well as geotechnical engineers and professionals."--Jacket.